2005
DOI: 10.1007/s11661-005-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of water cooling during the continuous casting of steel and aluminum alloys

Abstract: In both continuous casting of steel slabs and direct chill (DC) casting of aluminum alloy ingots, water is used to cool the mold in the initial stages of solidification, and then below the mold, where it is in direct contact with the newly solidified surface of the metal. Water cooling affects the product quality by (1) controlling the heat removal rate that creates and cools the solid shell and (2) generating thermal stresses and strains inside the solidified metal. This work reviews the current stateof-the-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 32 publications
1
58
0
Order By: Relevance
“…It has also been previously reported that water flow rate is one of the main process parameters that can change upon direct chill casting because increasing the water flow in the mould increases the heat-transfer rate, and thereby decreases the mould temperature [15,16]. Water-cooling affects the product quality by (1) controlling the heat removal rate that creates and cools the solid shell and (2) generating thermal stresses and strains inside the solidified metal [17]. When the cooling rate is slow, some of the large clusters of atoms in the liquid develop interfaces and become the nuclei for the solid grains that are to form.…”
Section: Water Flow Ratementioning
confidence: 97%
See 1 more Smart Citation
“…It has also been previously reported that water flow rate is one of the main process parameters that can change upon direct chill casting because increasing the water flow in the mould increases the heat-transfer rate, and thereby decreases the mould temperature [15,16]. Water-cooling affects the product quality by (1) controlling the heat removal rate that creates and cools the solid shell and (2) generating thermal stresses and strains inside the solidified metal [17]. When the cooling rate is slow, some of the large clusters of atoms in the liquid develop interfaces and become the nuclei for the solid grains that are to form.…”
Section: Water Flow Ratementioning
confidence: 97%
“…So water flow rate in continuous casting plays a key role in transforming heat from the mould and solidifying metal during the continuous casting of copper and copper alloys. It has also been previously reported that water flow rate is one of the main process parameters that can change upon direct chill casting because increasing the water flow in the mould increases the heat-transfer rate, and thereby decreases the mould temperature [15,16]. Water-cooling affects the product quality by (1) controlling the heat removal rate that creates and cools the solid shell and (2) generating thermal stresses and strains inside the solidified metal [17].…”
Section: Water Flow Ratementioning
confidence: 99%
“…Melt superheating treatment is an effective method of refinement grain [13]. In the past decades, the effects of melt superheating on aluminium and Magnesium alloy have been studied [14,15].…”
Section: Melt Temperaturementioning
confidence: 99%
“…The application of numerical computing for the analysis and identification of the existing processrelated problem can lead to finding an appropriate solution. It results in an improvement of production and the quality of products [1][2][3][4][5][6][7][8][9][10][11][12]. For the continuous casting of steel, it could be analysis of the effect of the interaction between the solidifying metal and the mould wall, the effect of the mould powder, or the effect of the non-metallic inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Many numerical models of the continuous steel casting process used in numerical computations are based upon material parameter average values, i.e. specific heat, viscosity, density [2,[12][13][14][15][16]. The use of average values within such a broad temperature range leads to a significant increase in the numerical error concerning the calculated temperature distribution; this is the basis for computing thermal stresses, examining the mould taper, the steel flow within the mould, or predicting cast strand defects.…”
Section: Introductionmentioning
confidence: 99%